Molecular aspects of aneuploidy in preimplantation human embryos: a mini-review - Stolakis, Vasileios; Bertero, Maria Celia (Annals of Research Hospitals, 2019)
Aneuploidy is a major obstacle in achieving successful pregnancies in in vitro fertilization (IVF) procedures. In practice, more than 50% of preimplantation embryos are aneuploid and unable to achieve viable pregnancy. Analysis of human sperm and oocytes has showed that aneuploidy in preimplantation embryos is predominantly caused by an error-prone meiotic chromosome segregation mechanism in oocytes. In reproductive aged women, aneuploidy rate in human oocytes is reaching 20–30%, in contrast to human sperm, that only 1–8% have an abnormal chromosomal content. Meiotic aneuploidy can occur from meiosis I (MI) non-disjunction, meiosis II (MII) non-disjunction and MI or MII pre-division. Multiple factors have been suggested to contribute to meiotic aneuploidy including maternal age and impaired cohesin complex formation. Maternal age is the major critical factor related to aneuploidy; 50% of the oocytes from advanced age women (≥40 years old) are aneuploid due to meiotic errors. The relationship between maternal age and altered recombination, which is entirely dependent on the context of chromosomes, can also contribute to development of aneuploidy. Genomic errors can also arise during post-fertilization mitotic divisions, resulting in embryonic mosaicism. The mechanisms leading to embryonic mosaicism during embryonic mitosis are; non-disjunction, anaphase lagging and endoreplication. Mosaicism exists in ~15–90% of all cleavage stage human embryos and in general, mitotic aneuploidies rise from 63% at the cleavage stage to 95% in blastocyst stage. Relaxation or absence of cell cycle checkpoints are possible mechanisms that have been hypothesized to account for mitotic aneuploidy in early human preimplantation embryos. Specifically, defects in spindle assembly checkpoint (SAC) and malfunction of cohesion complexes, can lead to premature chromosome separation, while delay in their removal may result in non-disjunction. Furthermore, extra-nuclear DNA formation generated from lagging chromosomes with severe DNA damage (i.e., micronucleation), may be a major mechanism of mitotic aneuploidy. Once source of aneuploidy involves paternal factor is related to mitotic aneuploidy, as severe sperm defects and advanced paternal age can increase the percentage of mitotic abnormalities in embryos. Further work and analysis into the molecular mechanisms that lead to meiotic and mitotic aneuploidy in preimplantation embryos, could inspire clinical strategies to reduce the occurrence of aneuploidy and consequently improve the success rates of IVF.